World Englishes in professional communication. Issue 1 (9th July 2019) - Bhatia, Vijay K.
Abstract: Communication in international professional contexts, whether in spoken, written, or digital form, often involves participants from a variety of contexts in terms of variations in their use of language and cultural norms, discourse strategies, and expectations of participating members of specific professional communities, and as such, invariably reflects a multi‐norm rather than a mono‐norm native model of language use. However, very little attention has been paid either in world Englishes (WE) or discourse analytical studies to communication in professional practice, in particular with a focus on text‐external contextual factors. The major emphasis has so far been on the analysis of textualisation of discourse. Drawing on recent insights from critical genre analysis (Bhatia, 2017), I would like to argue that discursive data from professional practice provides additional support and convincing argument in favour of Kachru's (1985, p. 30) call for multi‐norm standards in international communication and for a need to consider 'new paradigms and perspectives for linguistics and pedagogical research' in national as well as international contexts.